Stuttering: a case study in the scientific method - Hegde MN (Journal of All India Institute of Speech and Hearing, 1970)
Stuttering is one of the speech problems on which there is relatively more information in the literature.   And it is also a problem that has been studied from different angles and viewpoints.    In fact, the different approaches to stuttering are so varied that they are often contradictory.   Thus, for an objective examination, the literature on stuttering is a 'welter of confusion' (Rathna 1969).    This confusion, it seems, is not entirely due to the presence of different approaches, but rather to the weakness and the inherent contradictions of each of these approaches. In other words, there are not only mutually exclusive viewpoints, but each viewpoint suffers from a lack of internal consistency and also of empirical evidence.